Effectiveness of an Education Program on Knowledge of Primary School Teachers toward Mumps Disease - Haqi I. Mansoor1 , Kahtan H. Hussein2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to determine the effectiveness of an education program on primary school teachers’ knowledge toward mumps disease and to identify the relationship between the primary school teachers’ knowledge and some demographic variables. Quantitative research a quasi-experimental design (pre-post tests) has been used in the present study for the period of January 2018 to the end of June 2019. A nonprobability (purposive sample) sample of 60 teachers has been selected from 30 primary schools in Holy Kerbala City. The sample of the study was divided into two groups: (30) teachers for the study group, who have been exposed to the education program, and (30) teachers for the control group, who not exposed to the education program. The groups are almost matched relative to their characteristics. The questionnaire was submitted to the teachers for the pre-test before the implementation of the program. Post-test I was conducted immediately after that. Post-test II was conducted two months later. The findings of the data analysis indicate that the teachers’ knowledge among the study group improves as a result of the implementation of the education program. Among the control group, there is no significant difference in the level of teachers’ knowledge. The study recommends the cooperation between the Ministry of Education with the Ministry of Health to develop a national plan regarding mumps and other communicable diseases to raise the awareness of the school community (students, teaching, and non?teaching staff, and parents) regarding this diseases.